2020
DOI: 10.1007/s42770-020-00306-0
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and ecological niche modeling of the etiological agents of human sporotrichosis in Venezuela

Abstract: The geographical distribution and ecological niche of the two circulating species of the Sporothrix genus in Venezuela was established. For this, 68 isolates of Sporothrix spp. from patients of different regions of the country were analyzed. A molecular taxonomy analysis was conducted using a fragment of the calmodulin gene (CAL), and ITS regions, confirming the presence of S. schenckii (62%) and S. globosa (38%). Computational models of ecological niche for each species were obtained by the maximum entropy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Toriello et al [14] present a systematic review of sporotrichosis in Mexico that analyzes its epidemiology, geographic distribution, and diagnosis. Barreto et al [15] showed here the ecological niche of the two circulating species of the Sporothrix genus found in Venezuela. Rudramurthy et al [16] studied 63 cases of sporotrichosis of geographically diverse origin from India.…”
mentioning
confidence: 68%
“…Toriello et al [14] present a systematic review of sporotrichosis in Mexico that analyzes its epidemiology, geographic distribution, and diagnosis. Barreto et al [15] showed here the ecological niche of the two circulating species of the Sporothrix genus found in Venezuela. Rudramurthy et al [16] studied 63 cases of sporotrichosis of geographically diverse origin from India.…”
mentioning
confidence: 68%
“…(100%) found in Uruguay [ 124 ]. Finally, there were 4 reports from Venezuela with 452 cases of Sporothrix spp., and the Sporothrix complex was found in 220 of those cases (48.67%), S. schenckii sensu lato in 130 (28.76%), S. schenckii in 42 (9.29%), S. schenckii sensu stricto in 17 (3.76%), S. globosa in 39 (8.63%), 1 case of Ophiostoma stenoceras (0.22%) and 3 cases were ND (0.66%) [ 125 , 126 , 127 , 128 ].…”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
“…In Venezuela, Sporothrix spp. (80.04%), S. schenckii (13.38%), and S. globose (6.57%) were the types of Sporothrix agents [ 125 , 126 , 127 , 128 ].…”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
“…Currently, 53 Sporothrix species have been described [ 13 ], which are divided into two clades, one is “clinical or pathogenic”, isolated from human or animal cases; composed of S. schenckii of worldwide distribution, S. globosa is present in Argentina, Venezuela, United Kingdom, Spain, Italy, China, Japan, USA, and India [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. S. luriei is present in South Africa and S. brasiliensis is restricted to South America [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The remaining species are nested in an “environmental clade”, often associated with organic substrates such as soils with decaying plant remains, wood, or insects [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%